Research on the Influence Mechanism of the High-Steep Slope on the Deformation Characteristics of Bridge Substructure - Yufang Zhang; Hongyu Liu; Jian Li; Jiaming Li; Qidi Huang; Xianjie Ma (Advances in Civil Engineering)
With the development of the Chinese railway, the high-steep slope is irreversible to be faced; especially under severe conditions such as heavy rainfall and earthquake, this kind of slope is prone to geological disasters, which seriously affects the safety and stability of the bridge substructure. Aiming to this, long-term monitorization and numerical analysis were carried out in this research, and the influence mechanism of the high-steep slopes on the stress and deformation characteristics of the bridge structure was studied. The research results show that under the effect of rainfall and earthquake, the original stress balance in the high-steep slope is broken, and the possibility of landslide thrust increases; under the comprehensive impact of residual landslide thrust, traction force at slope foot, vertical gravity of bridge slab and vehicle, and the bridge cap will deform. Besides, the deformation of the bridge pier exceeds the allowable lateral displacement of the top of the bridge pier, reaching 111.7%∼112.4% of the limit, which seriously affects the stability of the bridge structure and the safety of the railway service. Therefore, by increasing the support strength of the slope foot and the diameter of the bridge pile foundation, the traction force of the slope foot can be reduced, and the sliding resistance of the bridge pile foundation can be improved so as the safety of the bridge structure can be promoted.